2012
DOI: 10.2527/jas.2011-4643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co-grazing dairy heifers with goats on animal performance, dry matter yield, and pasture forage composition1

Abstract: Mixed livestock grazing can offer an alternative management system for rearing dairy replacement heifers (Bos taurus). A 2-yr study was conducted during 2009 (yr 1) and 2010 (yr 2) to determine the effects of co-grazing Holstein heifers under rotational stocking with Boer × Kiko goats on animal performance, pasture DM yield, and botanical composition. Each year, 24 heifers (134 ± 6 d of age and 147.4 ± 31.2 kg BW in yr 1; 166 ± 11 d of age and 168.0 ± 27.6 kg BW in yr 2) and 6 goats (2 yr old and 39.7 ± 16.2 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…The large difference for the cattle-alone treatment was due to their near total avoidance of blackberry. This is similar to the findings of Dennis et al (2012), who noted a substantially higher presence of weeds in cattle-only pastures than in mixed cattle-and-goat pastures after being grazed for 2 yr.…”
Section: Treatmentsupporting
confidence: 89%
“…The large difference for the cattle-alone treatment was due to their near total avoidance of blackberry. This is similar to the findings of Dennis et al (2012), who noted a substantially higher presence of weeds in cattle-only pastures than in mixed cattle-and-goat pastures after being grazed for 2 yr.…”
Section: Treatmentsupporting
confidence: 89%
“…Therefore, the partial slaughter traits of Taihang black goats increase with age. The live weight of Taihang black goats slaughtered at the age of 2 was lower than that of goats (39.2 kg at the age of 2) reported by Dennis et al [15] in a grazing system. However, Hozza et al [16] reported lower live weights (mean of 18.57 kg) in crossbred goats that received different concentrate supplements and were slaughtered at the age of 21 months.…”
Section: Carcass Characteristicscontrasting
confidence: 61%
“…Se determinó mediante la recolección al azar de cinco muestras por pradera de 50g de forraje cortadas con tijeras a ras de suelo, de acuerdo con Dennis et al (2015). Cada muestra de forraje colectado estuvo conformada por diferentes especies vegetales presentes en la pradera, las cuales se separaron manualmente y fueron clasificadas como gramíneas, leguminosas, material vivo (verde) y muerto (seco), así como otras plantas.…”
Section: Composición Botánicaunclassified